Analisis Model Perilaku MEnabung Diujikan pada Nasabah Bank Syariah di Kota Serang - Asti Aini; Anita Anita; Siti Marfu'ah; Putri Intan Srijaya (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2023)
This study aims to test the Behavioral Planned theory with the direct and indirect influence of several factors that influence the decisions of Islamic Bank customers. This research uses analytical techniques using the Smart PLS version 3.0 software . The results of the study reveal that financial attitudes (t-value: 8,868); subjective norms (t-values: 5,809); and behavioral control (t-value: 2,462) have a direct effect on saving behavior, and demographic variables (age, education and income) are a moderating construct in the relationship between attitudes and saving behavior (3,039 >1,96); the relationship between subjective norms and saving behavior (4,079 >1,96); the relationship between behavioral control and saving behavior (3,718 > 1,96) at alpha 5.%